What is deep tropical mycosis? An underestimated entity with serious problems - Abdulla, Karzan A.; Saeed, Rebeen R. (International Journal of Advances in Medicine, 2017)
There are many fungal infections which have been described in the literature but only a small number of them causes diseases in human being. The clinical manifestation is diverse and the spectrum of severity ranges from simple localized infections to severe systemic disease. Some of these fungal infections characteristically occur more frequently in tropical countries and hence they are called tropical mycosis; however even these kinds of mycotic infections may be seen outside the tropical countries due to migration and travel. In this article we try to review the deep tropical mycosis and highlight the important aspects of diseases classified under this entity, we also try to address some of the issues related to these illnesses and demonstrating their management in summary.